Ozone Therapy for Tumor Oxygenation: a Pilot Study. Issue 1 (2004) - Clavo, Bernardino; Pérez, Juan L.; López, Laura; Suárez, Gerardo; Lloret, Marta; Rodríguez, Victor; Macías, David; Santana, Maite; Hernández, María A.; Martín-Oliva, Roberto; Robaina, Francisco
Abstract : Tumor hypoxia is an adverse factor for chemotherapy and radiotherapy. Ozone therapy is a non-conventional form of medicine that has been used successfully in the treatment of ischemic disorders. This prospective study was designed to assess the effect of ozone therapy on tumor oxygenation. Eighteen subjects were recruited for the study. Systemic ozone therapy was administered by autohemotransfusion on three alternate days over one week. Tumor oxygenation levels were measured using polarographic needle probes before and after the first and the third ozone therapy session. Overall, no statistically significant change was observed in the tumor oxygenation in the 18 patients. However, a significant decrease was observed in hypoxic values ≤10 and ≤5 mmHg of pO2. When individually assessed, a significant and inverse non-linear correlation was observed between increase in oxygenation and the initial tumor pO2 values at each measuring time-point, thus indicating that the more poorly-oxygenated tumors benefited most (rho = −0.725; P = 0.001). Additionally, the effect of ozone therapy was found to be lower in patients with higher hemoglobin concentrations (rho = −0.531; P < 0.034). Despite being administered over a very short period, ozone therapy improved oxygenation in the most hypoxic tumors. Ozone therapy as adjuvant in chemo-radiotherapy warrants further research.